PENGARUH KONSEP DIRI TERHADAP PEMECAHAN MASALAH BAGI SISWA KELAS X DI SMA NEGERI JAKARTA TIMUR - Ernawati, Renatha (Jurnal Dinamika Pendidikan, 2015)
The population of study was the students of class X students of SMAN East Jakarta, amounting to 8 schools and the total number of students was 295. Random sampling technique of test sample was used and obtained by 40 students and the study sample as many as 60 students. In order to answer the problems, the writer used a survey and correlation methods. What is meant by the correlation method is to find the relationship between the variables X into Y and independent variables being the dependent variable. Based on the results of hypothesis testing is known that there is a positive and significant relationship between the effects of self-concept to problem solving for. With a correlation coefficient (R) of 0.707 which indicates that the correlation between the two variables was strong, and the coefficient of determination (R Square) of 0.499. This means that the variable self-concept affects students problem-solving of 49.9%, while the remaining 50.1% is influenced by other factors.Keywords : Self-Concept, Problem-Solving